Kajian Daya Dukung Atraksi Wisata di Taman Wisata Alam Lembah Harau Sumatera Barat - Edrian Junarsa; Syartinilia Wijaya; Nurhayati Hadi Susilo Arifin (http://arl.faperta.ipb.ac.id/, 2023)
The Harau Valley Natural Tourism Park is one of the most popular destinations for local, domestic and foreign tourists in West Sumatra. The number of Harau Valley Natural Tourism Park tourists in 2018 increased by 37% from the previous year, which was 358,827 tourists. Increasing demand for tourism objects, especially in the Harau Valley Natural Tourism Park will unavoidably leads to further development of the park for tourism activities. Thus, consequently it will affect the park and its surroundings ecologically, socially, and economically. Studies on the carrying capacity of tourist areas are needed to minimize the impact caused by tourism activities. The purpose of this study is to identify and analyze the carrying capacity of the tourist area in the Harau Valley Natural Tourism Park. Data was collected using a survey method, namely field observations and literature studies which were then analyzed using the Douglass 1975 formula to identify carrying capacity for each tourist attraction. The results of the analysis of the carrying capacity of each tourist attraction were (1) natural recreation 85,056 people/year, (2) Boating is 7,802 people/year, (3) Swimming is 12,217 people/year, (4) Camping is 25,460 people/year, (5) Education and Research is 99,744 people/year, and (6) Photo hunting is 84,890 people /year. Hopefully, the results of the study can be used as future considerations in the development of the Harau Valley natural tourism park.